2.4 Whole exome sequencing of growth restricted offspring identifies gene variants implicated in maturity onset diabetes of the young. (9th June 2014) - Hillman, SL; Smart, MC; Bacchelli, C; Ocaka, L; Williams, DJ
Abstract : Background: The fetal insulin hypothesis suggests that poor fetal growth and diabetes are two phenotypes of genetically determined insulin resistance (IR). Evidence for the hypothesis arises through the study of mutations in maturity-onset diabetes of the young (MODY). Genetic inheritance of a mutation in glucokinase (a MODY gene) results in lower offspring birthweight if inherited through the father. We have previously shown that men, at the time of fathering a growth restricted pregnancy, are more insulin resistant. These findings support the hypothesis that inheritance of a genetic variant passed from father to offspring will result in fetal growth restriction (FGR) and paternal diabetes risk. Methods: In this study we used whole exome sequencing (WES) of DNA from 10 growth restricted offspring, in order to identify novel and rare variants in recognised MODY genes that might be influencing fetal growth. Results were validated with Sanger sequencing or Taqman genotyping. Results: In 2 of the 10 offspring sampled, single point heterozygous mutations were identified in MODY recognised genes ( HNF1β and NOTCH2 ). These variants were rare and predicted to be pathogenic. In a 3 rd case, 2 rare heterozygous mutations in synergistically acting MODY genes ( HNF1α and HNF4α ) were identified. In a 4 th case a very rare homozygous MODY mutation in KCNJ11 was identified. Conclusions: Through WES, rare genetic variants in genes associated with MODY were discovered in 4/10 separate offspring affected by FGR. Whilst proof of cause is required they are implicated in growth restriction through their predicted pathogenicity, rareness and known biological mechanisms.